PEMBELAJARAN BERBASIS PROYEK DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR: STUDI LITERATUR - Surya Handika, Aditya; Mulyadiprana, Ahmad; Merliana, Anggit (STKIP Subang, 2026)
This study aims to analyze the role of Project Based Learning (PjBL) in developing elementary school students’ critical thinking skills through a literature review approach. Critical thinking is an essential 21st-century skill that needs to be developed from an early age; however, in practice, students' critical thinking skills remain relatively low due to teacher-centered learning. This study employs a qualitative approach using a literature review method by examining relevant scientific journals and books. Data collection was carried out through the stages of identification, selection, and analysis based on specific criteria, including empirical studies focusing on elementary school students, Project Based Learning, and critical thinking skills. The data were analyzed using descriptive qualitative techniques by grouping, comparing, and synthesizing the findings of previous studies. The results indicate that Project Based Learning is effective in improving students’ critical thinking skills through active involvement in problem-solving, analysis, and evaluation processes. In addition, PjBL enhances students’ collaboration, communication, and responsibility in learning. Therefore, Project Based Learning can be considered an effective alternative learning model to improve the quality of learning in elementary schools.